2008
DOI: 10.1590/s0100-204x2008000800014
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética estimada entre diplóides de banana por meio de marcadores microssatélites

Abstract: Resumo -O objetivo deste trabalho foi estimar a divergência genética entre 38 diplóides de banana do programa de melhoramento da Embrapa Mandioca e Fruticultura Tropical, incluindo genótipos melhorados, cultivados e selvagens, por meio de 15 marcadores microssatélites ou SSR. As similaridades genéticas, com base no coefi ciente de Jaccard, foram utilizadas para fazer o agrupamento dos genótipos pelo método UPGMA. O número de alelos obtidos foi 113, com média de 7,53 alelos por iniciador. A similaridade genétic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
1
15
0
7
Order By: Relevance
“…Therefore, assessment of Musa genetic variability solely by using SSR markers continues to be widely used (e.g., Amorim et al, 2008;Jesus et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, assessment of Musa genetic variability solely by using SSR markers continues to be widely used (e.g., Amorim et al, 2008;Jesus et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The authors noted that some genotypes were grouped according to geographical origins, while others had no other relationship. Amorim et al (2008) using SSR markers and diploid genotypes, also found no complete separation among improved, cultivated, and wild hybrids, and some diploids were grouped based only in their geographical origin. In this study, there was no separation of genotypes based solely on geographic origin, but genotypes were grouped based on their genomic constitution.…”
Section: Genetic Diversity Analysis Using Ssr and Issr Markersmentioning
confidence: 99%
“…Dentre os marcadores existentes, os microssatélites (SSR) têm sido considerados os ideais para a caracterização e a avaliação da variabilidade genética, são abundantes, dispersos ao acaso no genoma, lócus específico, codominantes e multialélicos. Suas aplicações nos estudos com banana incluem a genotipagem, taxonomia e evolução, e saturação de mapas de ligação (AMORIM et al, 2008;JESUS et al, 2009).…”
Section: Introductionunclassified